Competition dependence of retrieval-induced forgetting in motor memory. - Tempel, Tobias; Aslan, Alp; Frings, Christian (Memory & Cognition, 2016)
In two experiments, we examined the competition dependence of retrieval-induced forgetting (RIF) in motor memory. Participants learned sequential finger movements as responses to letter stimuli. The learning phase comprised two parts. In both parts, half of the motor sequences were to be executed at one of two locations (the left or right side of a keyboard) by pressing the corresponding response keys. Retrieval practice of half of the motor sequences at one location induced forgetting of the nonpracticed motor sequences at that location. However, RIF was prevented in Experiment 1 when retrieval practice took place before the nonpracticed items had even been encoded. In Experiment 2, RIF was prevented by intentionally forgetting the nonpracticed motor sequences prior to retrieval practice. These results suggest that precluding competition by related items during retrieval practice precluded them from being affected by RIF. The present findings support an inhibitory account and speak against the alternative assumptions that associative blocking or a mental context change causes RIF.